Análisis de las causales de nulidad en el Estado de Quintana Roo - Carrillo Medina, Mayra San Román (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The State of Quintana Roo, through the Decree 121, published in the official State newspaper, on September 20, 1995, was published in the code of institutions and procedures election of the State of Quintana Roo. Said Ordinance proposed the creation of the State Electoral Council and the Electoral Tribunal, agencies that would be responsible to prepare and solve the State elections, is regulated, within the book fifth called "of LAS NULLITIES and of the system of means of challenge and of the sanctions administrative". The creation of the Electoral Court of Quintana Roo is given by Decree number 07, dated 16 July 2002, published in the newspaper official of State 17 of July 2002, by which the X legislature of the free State and sovereign of Quintana Roo. The Electoral Tribunal since its creation is the body specializing in electoral matters, which is responsible for knowing and substantiate all means of challenges that arise during the development of the electoral process, from the stage of preparation to the Declaration of results.

En el estado de Quintana Roo, a través del Decreto 121, publicado en el Periódico Oficial del Estado, el día 20 de septiembre de 1995, se publicó el Código de Instituciones y Procedimientos Electorales del Estado de Quintana Roo. En dicho ordenamiento se propuso la creación del Consejo Estatal Electoral y del Tribunal Electoral, organismos que se encargarían de preparar y resolver las elecciones estatales, se reguló, dentro del Libro Quinto denominado “DE LAS NULIDADES Y DEL SISTEMA DE MEDIOS DE IMPUGNACION Y DE LAS SANCIONES ADMINISTRATIVAS”. La creación del Tribunal Electoral de Quintana Roo se da mediante decreto número 07, de fecha 16 de julio del 2002, publicada en el Periódico Oficial del Estado 17 de julio del 2002, por el que la X Legislatura del Estado Libre y Soberano de Quintana Roo. El Tribunal Electoral desde su creación es el órgano especializado en materia electoral que se encarga de conocer y sustanciar todos los medios de impugnaciones que se presenten durante el desarrollo del proceso electoral, desde la etapa de preparación hasta la declaración de resultados.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2014-1126; Causales; Nulidad; Impugnación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/576